1992
DOI: 10.1016/0921-5093(92)90047-5
|View full text |Cite
|
Sign up to set email alerts
|

Thermal evidence for the structural instability in Ni3Al alloys

Abstract: The thermal expansion coefficient (a) and calorimetric data were obtained as a function of temperature in order to clarify some of the significant variations reported with regard to these values in the literature. Stoichiometric and off-stoichiometric compositions of Ni3Al alloys (with and without boron addition) were investigated. Dilatometric experiments were performed on all the alloys and the a values were estimated over the temperature range from ambient to 1000 °C. Two runs were made on each sample under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 12 publications
(15 reference statements)
0
2
0
Order By: Relevance
“…Ref. [25] Ref. [26] As a macroscopic characterization, thermal expansion is essentially caused by the atomic vibration in the lattice.…”
mentioning
confidence: 99%
“…Ref. [25] Ref. [26] As a macroscopic characterization, thermal expansion is essentially caused by the atomic vibration in the lattice.…”
mentioning
confidence: 99%
“…Williams et al [19] have found no significant variation in well-annealed Ni 3 Al containing either 24 or 25 at.% Al. However, the measurements by Ramesh et al [20], up to 1000 C, have shown the CTE of Ni-24 at.% Al to be slightly lower than that of stoichiometric Ni-25 at.% Al. However, Rao et al [21] report that the CTE shows an increase with lower Al concentrations up to 1000 C, and attributes the increase to a larger number of vacancies at off-stoichiometric compositions.…”
Section: Cte Of Ni 3 Almentioning
confidence: 85%